On the number of eigenvalues for parameter‐dependent diffusion problem on time scales. (8th August 2020) - Gulsen, Tuba; Jadlovská, Irena; Yilmaz, Emrah
Abstract : In this study, we consider parameter‐dependent diffusion eigenvalue problem on time scales. An upper bound on the number of eigenvalues for this problem on a finite time scale is given.